Organizing democratic choice party representation over time - Budge, Ian.; European Consortium for Political Research (Oxford : Oxford University Press, 2012)
'Organizing Democratic Choice' offers a new, invigorating theory of how democracy actually works. It also presents a challenge to democratic pessimists who would have everyone believe that neither political parties nor mass publics are up to the tasks that democracy assigns them.
At foot of title: ECPR.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Representative government and representation; Democracy; Policy sciences; Comparative government